Factors affecting the intention to use blog by students at secondary and tertiary educations - Landani, Zahra Mardani; Syed Hassan, Sharifah Sariah (Asian Economic and Social Society (AESS), 2013)
This study aimed to investigate factors affecting the intention to use blog and ease of it’s use at secondary and tertiary educations. Technology Acceptance Model (TAM) by Davis (1989) has been adopted in designing the theoretical framework for the study. This framework is applied to examine the significant differences between level of study related to factors affecting the intention to use blog namely the academic benefits, the social benefits, and ease of its use. One hundred students completed the survey questionnaire and responses to the 24 items were analysed. The results suggest that only one factor ( the academic benefits) was found to have a significant influence on the intention to use blog. In addition it was also found that there is a significant difference between perceived academic benefits of blogging at school and university levels of education